A Study on the Epidemiology and Aetiology of Acute Gastroenteritis in Adult Patients Presenting at the Infectious Diseases Hospital in Tirana, Albania - Gentian P. Stroni; Majlinda M. Dhimolea; Silva F. Bino; Pëllumb S. Pipero; Dhimiter V. Kraja; Suela Y. Sallavaci (Balkan Medical Journal, 2014)
Background: Acute gastroenteritis remains a common cause of hospital emergency room visits in Albania. However, the aetiology of severe gastroenteritis leading to hospitalization in adults frequently remains unclear.